Interactive Materials for Bidirectional Redox‐Based Communication. Issue 18 (31st March 2021) - Li, Jinyang; Wang, Sally P.; Zong, Guanghui; Kim, Eunkyoung; Tsao, Chen‐Yu; VanArsdale, Eric; Wang, Lai‐Xi; Bentley, William E.; Payne, Gregory F.
Abstract: Emerging research indicates that biology routinely uses diffusible redox‐active molecules to mediate communication that can span biological systems (e.g., nervous and immune) and even kingdoms (e.g., a microbiome and its plant/animal host). This redox modality also provides new opportunities to create interactive materials that can communicate with living systems. Here, it is reported that the fabrication of a redox‐active hydrogel film can autonomously synthesize a H2 O2 signaling molecule for communication with a bacterial population. Specifically, a catechol‐conjugated/crosslinked 4‐armed thiolated poly(ethylene glycol) hydrogel film is electrochemically fabricated in which the added catechol moieties confer redox activity: the film can accept electrons from biological reductants (e.g., ascorbate) and donate electrons to O2 to generate H2 O2 . Electron‐transfer from an Escherichia coli culture poises this film to generate the H2 O2 signaling molecule that can induce bacterial gene expression from a redox‐responsive operon. Overall, this work demonstrates that catecholic materials can participate in redox‐based interactions that elicit specific biological responses, and also suggests the possibility that natural phenolics may be a ubiquitous biological example of interactive materials. Abstract : A redox‐active catechol‐based film can autonomously synthesize diffusible H2 O2 signals that enable interactive communication with biology. The reducing redox activities of a bacterial culture provide the electrons that poise this film for subsequent electron‐donation to O2 to generate the H2 O2 signaling molecule that induces redox‐responsive gene expression.